Rewriting the book in the index: what does this mean?. (1st December 2020) - Ullstrom, Stephen
Abstract : A common admonishment for indexers is not to rewrite the book in the index. Stephen Ullstrom examines this advice in terms of exhaustivity, depth of indexing, and specificity. He concludes that instead of focusing on what the index should not be, we should focus on what it should be, which is clear, comprehensive, and appropriate for the text and audience.